Urban and Rural accommodation in Santa Rosa de Cabal (Risaralda, Colombia) (2019)
The accommodations are constitute in a driving factor of the touristicdisplacements around the world and result critics for the catchment oftourists in Colombia. Particularly in Santa Rosa de Cabal. This article hasas objective to describe the quality of the services provided in the rural andurban accommodations, using a structured checklist according to the lawNTSH 006, for the owners and administrators with a view of proposing somerecommendations to increase the quality of hotel service provided by themunicipality. There are low levels of certification among the hotels participants:only the 32% of the accommodations counts with any. The quality processes arepresent in factors as edification, security, the room and their baths, maintenanceand reservations.